The Influence Of Emotional Intelligence And Learning Discipline On Ips Economics Study High School Ekasakti Padang - Detman Detman (Fakultas Sastra Universitas Ekasakti, 2018)
This research is motivated by the problem of emotional intelligence and discipline of learning on learning outcomes of accounting SMA Ekasakti. The purpose of this study was to determine and describe the influence of emotional intelligence and discipline of learning on learning outcomes of accounting students of class XI Social SMAN Ekasakti Padang. The hypothesis of this study is suspected that there is positive and significant correlation between emotional intelligence and discipline of learning on learning outcomes of accounting students of class XI Social SMA Ekasakti Padang. This research is a quantitative approach Correlational the entire population of students of class XI Social SMA Ekasakti Padang as many as 78 students. Sampling was done by way of random sampling technique in which the individual is drawn at random from the class XI IPS1, IPS2 to class XI XI IPS3. Samples were taken by 43 students by using Slovin formula. The independent variable in this paper is emotional intelligence (X1), the discipline of learning (X2) and the dependent variable is the student learning outcomes (Y). Data emotional intelligence and discipline of student learning gained from the questionnaire / questionnaire. Analysis of the data used is a statistical data analysis techniques to find the influence of emotional intelligence and discipline of learning on learning outcomes and tested multiple regression analysis and coefficient of determination. From the results penalitian, multiple regression coefficients obtained for emotional intelligence variable Y = 88.580 + 0.051 + e shows the r-sig 0.000 alpha ≤ 0.05. and the regression coefficient for the variable Y = 87.580 learn discipline + 0.077 + e shows r-sig ≤ 0.001 alpha of 0.05. R Square of 0.704 or 70.40%. So it is concluded that in this penalitian a positive influence of emotional intelligence and discipline of learning on learning outcomes of accounting students of class XI Social SMAN Ekasakti. The results of this study are expected to be material information and the input of the academic community, especially the teachers as teachers, parents and the community in order to improve emotional intelligence and discipline of learning on the learner.